Confronting desire psychoanalysis and international development - Kapoor, Ilan (Cornell University Press, 2020)
"This book critically analyzes important current issues in international development-growth, poverty, inequality, participation, consumption, corruption, gender, race, LGBT politics, revolution, universalism-by deploying key psychoanalytic concepts-enjoyment, fantasy, antagonism, fetishism, envy, drive, perversion, hysteria. It draws on the work of Lacan and Žižek, and on psychoanalytic postcolonial and feminist scholarship"--